(3fMh Yde GbJUGO LOjO Yf GdefTCIs - (3ejTGd(B, (3OGjJQjTs; (3fGOQ GOQjS GdJd(B, s ((3YeGf(B:s (3OGQ GdcJGH GdMOjK(B,s, 1998)
1) (3eG hQGA JcGdja GdUabI (B: (3GdNdajI (B: (3fehPL JcdaI GdUabI , (B2) (3eG hQGA JcGdja GdUabI (B: (3MOhO GdefTCI (B: (3JWhQ GdefTCI , GdGfOeGL GdehaQJTcjdI ef faS GdNOeI h (B/ (3Ch GdefJhL h GdefTCI , GdGfOeGL GdehaQ dNOeGJ h (B/ (3Gh efJhLGJ efJfhYI dGShGb eNJdaI h GdefTCI , THg GdGfOeGL h GdefTCI (B3) (3Yde EbJUGO LOjO Yf GdefTCI (B: (3GdefTCI h GdfXQjI GdGbJUGOjI , GdefTCI cfSb , GdSjGSI GdGbJUGOjI h GdefTCI (B.s
(3ghGeT U(B. 205 (3, HjHdjhZQGajG U(B.217 (3; agQS GdGYdGe U(B.237(3U(B.(3; agQS GdehGVjY U(B.243s
Keywords: (3GdGbJUGOs; (3GdUabGJs